2007
DOI: 10.1007/s11145-007-9088-4
|View full text |Cite
|
Sign up to set email alerts
|

The developing mental lexicon: evidence from morphological priming of irregular Hebrew forms

Abstract: This study investigated the development of automatic word recognition processes, in particular the development of the morphological level of processing. We examined masked priming of Hebrew irregular forms at two levels of reading experience. Both third-and seventh-grade children showed morphological priming for defective roots when primes and targets conformed to the canonical morphological structure, containing all three letters of the roots, and also when the surface form of the primes and targets contained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 51 publications
3
22
1
Order By: Relevance
“…These authors suggested that children were indeed sensitive to the morphological structure of words during reading based on these findings. Similar results were reported by Schiff, Raveh, and Kahta (2008) for third through seventh graders reading Hebrew and by Verhoven et al (2006) for third and sixth graders learning Dutch. However, few (if any) such studies have been conducted on this issue in Chinese.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…These authors suggested that children were indeed sensitive to the morphological structure of words during reading based on these findings. Similar results were reported by Schiff, Raveh, and Kahta (2008) for third through seventh graders reading Hebrew and by Verhoven et al (2006) for third and sixth graders learning Dutch. However, few (if any) such studies have been conducted on this issue in Chinese.…”
Section: Introductionsupporting
confidence: 90%
“…On the word level, analytic processing and the processing of specific morphemes have been documented in several studies of adults in both alphabetic languages, such as English (e.g., Marslen-Wilson, Tyler, Waksler, & Older, 1994;Taft, 2004) and Chinese (e.g., Zhou & Marslen-Wilson, 1995;Zhou, Marslen-Wilson, Taft, & Shu, 1999). Additional studies suggest that children's word processing is also influenced at least in part by the morphemes within the words (e.g., Casalis, Dusautoir, Cole, & Ducrot, 2009;McCutchen, Logan, & Biangardi-Orpe, 2009;Schiff, Raveh, & Kahta, 2008;Verhoeven, Schreuder, & Haarman, 2006). For instance, Casalis, Dusautoir, Cole, and Ducrot (2009), using a priming lexical decision paradigm, found that French fourth graders showed a significant positive priming effect when targets (derived words) were preceded by primes that shared a morphological relationship with the targets even though this effect could not be distinguished from the purely orthographic effect at a short prime duration.…”
Section: Introductionmentioning
confidence: 96%
“…Similarly, French second graders are more accurate when reading aloud pseudowords made up of morphemes (e.g., mordage, where an equivalent in English could be ''bitage'') than pseudowords with only a suffix (e.g., soumage, where an equivalent in English could be ''somage'') (Marec-Breton, Gombert, & Colé, 2005). Morphological processing in reading has also been evidenced in Hebrew morphology in third and seventh graders (Schiff, Raveh, & Kahta, 2008) and in the Italian regular orthography in third to fifth graders (Burani, Marcolini, & Stella, 2002).…”
Section: Introductionmentioning
confidence: 93%
“…Even second and third graders showed strong visual morphological priming when the prime and the target words shared a root (Schiff, 2003;Schiff, Raveh, & Kahta, 2008;Yamin & Raveh, 2005). In a recent study, Schiff et al (2008) further examined the development of the morphological organization of the mental lexicon of young readers by using morphologically irregular Hebrew forms within a paradigm previously used by Velan, Frost, Deutsch, and Plaut (2005) to test adult Hebrew readers.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Even second and third graders showed strong visual morphological priming when the prime and the target words shared a root (Schiff, 2003;Schiff, Raveh, & Kahta, 2008;Yamin & Raveh, 2005). In a recent study, Schiff et al (2008) further examined the development of the morphological organization of the mental lexicon of young readers by using morphologically irregular Hebrew forms within a paradigm previously used by Velan, Frost, Deutsch, and Plaut (2005) to test adult Hebrew readers. Similar to the results found for adults (Frost, Deutsch, & Forster, 2000;Velan et al, 2005), the priming pattern observed with third-and seventh-grade children suggested the existence of allomorphic representations for irregular roots.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%